2017
DOI: 10.1071/an15024
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different levels of crude protein on the pathophysiology of Haemonchus contortus infection in 2-year-old Boer dry does under confined conditions

Abstract: The effect of dietary protein supplementation on the pathophysiology of a single Haemonchus contortus infection in 2-year-old Boer dry does under confined conditions was examined. Twenty-four does were randomly confined in individual pens and allocated into three groups balanced by their liveweight. The goats in the Control group were offered a basal diet whereas goats in Treatments 1 and 2 were fed the basal diet plus 25% and 50% dietary protein increments, respectively. Each animal was orally administrated 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…These results are similar to those found in the current literature whereas lambs supplemented on pasture with soyhulls or DDGS had lesser FAMACHA eye scores and greater PCV values when compared with non-supplemented control lambs ( Felix et al, 2012 ). Conversely, in evaluating the effect of different levels of protein supplementation using oaten and lucerne chaff in Boer goats administered a single dose of H. contortus at a rate of 100 L 3 larvae/kg of live BW, protein supplementation did not have an effect on goat PCV ( Can et al, 2017 ). Furthermore, regardless of infection status (infected vs. non infected), supplemental protein has shown to improve lamb PCV ( Datta et al, 1998 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are similar to those found in the current literature whereas lambs supplemented on pasture with soyhulls or DDGS had lesser FAMACHA eye scores and greater PCV values when compared with non-supplemented control lambs ( Felix et al, 2012 ). Conversely, in evaluating the effect of different levels of protein supplementation using oaten and lucerne chaff in Boer goats administered a single dose of H. contortus at a rate of 100 L 3 larvae/kg of live BW, protein supplementation did not have an effect on goat PCV ( Can et al, 2017 ). Furthermore, regardless of infection status (infected vs. non infected), supplemental protein has shown to improve lamb PCV ( Datta et al, 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is in support of the concept that regardless of whether the infection was experimentally induced or naturally acquired through grazing, lambs provided supplemental protein have lesser FEC when compared to non-supplemented lambs ( Abbott et al, 1988 ; Wallace et al, 1995 ; Strain and Stear, 2001 ). Similarly, Boer does artificially infected with a single dose of 100 H. contortus L 3 larvae/kg BW, demonstrated a negative correlation between FEC and supplemental protein such that FEC decreased linearly with increasing increments of supplemental protein in the basal diet, however, the H. contortus treatment used did not cause pathogenic effects in the Boer does ( Can et al, 2017 ). Under conditions where sheep are continuously ingesting H. contortus L 3 larvae from grazed forage, Bassetto et al (2018) demonstrated that giving grazing ewes supplemental protein decreased ewe FEC and improved the effect of a H. contortus specific vaccine (Barbervax).…”
Section: Discussionmentioning
confidence: 99%